Ophthalmic artery Doppler at 35–37 weeks' gestation in pregnancies with small or growth‐restricted fetuses. (4th March 2022) - Abdel Azim, S.; Sarno, M.; Wright, A.; Vieira, N.; Charakida, M.; Nicolaides, K. H.
ABSTRACT: Objectives: First, to compare the ophthalmic artery peak systolic velocity (PSV) ratio at 35–37 weeks' gestation among women who delivered small‐for‐gestational‐age (SGA) or growth‐restricted (FGR) neonates in the absence of hypertensive disorders, women who developed pre‐eclampsia (PE) or gestational hypertension (GH) and those without SGA, FGR, PE or GH. Second, to examine the association of PSV ratio with placental growth factor (PlGF) and mean arterial pressure (MAP). Third, to assess the associations of PSV ratio, PlGF and MAP with birth‐weight Z ‐score and percentile. Methods: This was a prospective observational study in women attending for a routine hospital visit at 35 + 0 to 36 + 6 weeks' gestation. This visit included recording of maternal demographic characteristics and medical history, ultrasound examination of fetal anatomy and growth, and measurement of maternal ophthalmic artery PSV ratio, first (PSV1) and second (PSV2) peaks of systolic velocity, MAP and serum PlGF. The values of PSV ratio, MAP and PlGF were converted to multiples of the median (MoM) or delta values, and the median MoM or delta of these variables in the SGA, FGR, PE and GH groups were compared with those in the unaffected group. Regression analysis was used to examine the relationship of PSV ratio delta, PlGF MoM and MAP MoM with birth‐weight Z ‐score after exclusion of PE and GH cases. Regression analysis was also used to examine the association of PSV ratio delta with log10 PlGF MoM and log10 MAP MoM. Results: The study population included 2287 pregnancies, of which 1954 (85.4%) were not affected by FGR, SGA, PE or GH, 49 (2.1%) were complicated by FGR in the absence of PE or GH, 160 (7.0%) had SGA in the absence of FGR, PE or GH, 60 (2.6%) had PE and 64 (2.8%) had GH. Compared with unaffected pregnancies, in both the FGR and SGA groups, the means of PSV ratio delta (0.042 (95% CI, 0.007–0.076) and 0.032 (95% CI, 0.016–0.049), respectively) and MAP MoM (1.028 (95% CI, 1.006–1.050) and 1.048 (95% CI, 1.035–1.060), respectively) were increased, while the mean of PlGF MoM was decreased (0.495 (95% CI, 0.393–0.622) and 0.648 (95% CI, 0.562–0.747), respectively). However, the magnitude of these changes was smaller than in the PE and GH groups. Ophthalmic artery waveform analysis revealed that the predominant feature of pregnancies complicated by SGA in the absence of hypertensive disorders was a reduction in PSV1, whereas, in those with hypertensive disorders, there was an increase in PSV2. In non‐hypertensive pregnancies, there were linear inverse associations of PSV ratio delta and MAP MoM with birth‐weight Z ‐score, with increased values in small neonates and decreased values in large neonates. There was a quadratic relationship between PlGF MoM and birth‐weight Z ‐score, with low PlGF levels in small neonates and high PlGF levels in large neonates. There was a significant correlation of ophthalmic artery PSV ratio delta with both log10 MAP MoM (0.124 (95% CI, 0.069–0.178)) and log10 PlGF MoM (−0.238 (95% CI, −0.289 to −0.185)). Conclusion: Assuming that the ophthalmic artery PSV ratio is a reflection of the interplay between cardiac output and peripheral vascular resistance, the linear association between PSV ratio and birth‐weight Z ‐score in non‐hypertensive pregnancies suggests the presence of a continuous physiological relationship between fetal size and cardiovascular response rather than a dichotomous relationship between high peripheral resistance and low cardiac output in small compared with non‐small fetuses. © 2022 International Society of Ultrasound in Obstetrics and Gynecology.